ESTRATEGIAS DE APROVISIONAMIENTO DE NIDOS EN LA AVISPA SPHEX LATREILLEI LEPELETIER (HYMENOPTERA: SPHECIDAE - Chiappa, E.; Toro, H. (Acta Entomológica Chilena, 2022)
In a large nesting aggregation of the ground burrowing wasp Sphex latreillei, the females provisioned their nests either hunting orthopteran preys or stealing them to olhers wasps. As a result some agonistic interactions are produced. Evolutionary significance of these alternative strategies are discussed